2002
DOI: 10.1677/joe.0.1720527
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 11 beta-hydroxysteroid dehydrogenase type 2 activity in ovine placenta by fetal cortisol

Abstract: The effect of fetal cortisol on the activity of the type 2 isoform of the enzyme, 11 -hydroxysteroid dehydrogenase (11 -HSD2), was examined in ovine placenta and fetal kidney by measuring tissue 11 -HSD2 activity during late gestation when endogenous fetal cortisol levels rise and after exogenous cortisol administration to immature fetuses before the prepartum cortisol surge. Placental 11 -HSD2 activity decreased between 128-132 days and term (]145 days of gestation) in association with the normal prepartum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 54 publications
1
52
0
1
Order By: Relevance
“…This enzyme, therefore, is a key factor in limiting foetal exposure to maternal glucocorticoids. Its placental activity is regulated by nutritional and endocrine factors (Clarke et al, 2002;Seckl, 2001). Thus, it follows that increased foetal glucocorticoid exposure, therefore, occurs due to increased maternal glucocorticoid levels, decreased placental 11βOHSD-2 activity or increased glucocorticoid output by the foetal adrenal.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme, therefore, is a key factor in limiting foetal exposure to maternal glucocorticoids. Its placental activity is regulated by nutritional and endocrine factors (Clarke et al, 2002;Seckl, 2001). Thus, it follows that increased foetal glucocorticoid exposure, therefore, occurs due to increased maternal glucocorticoid levels, decreased placental 11βOHSD-2 activity or increased glucocorticoid output by the foetal adrenal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, glucocorticoids can both up-and downregulate placental timing and mode of administration (Kerzner et al 2002, Ma et al 2003, van Beek et al 2004. Another study reported a reduction in ovine placental 11 -HSD2 activity in response to chronically elevated glucocorticoid levels (Clarke et al 2002). Importantly, none of the above studies investigated immediate regulation of placental 11 -HSD2 activity in response to glucocorticoids, although this presumably would be the most efficient way to inactivate stress-induced corticosteroids from maternal blood.…”
Section: Discussionmentioning
confidence: 99%
“…11b HSD-2 deactivates cortisol through conversion to the less active cortisone (Stewart et al 1995, Klemcke & Christenson 1996, Clarke et al 2002. Placental 11b HSD-2 is particularly important because maternal GC levels are up to tenfold higher than in the fetus, therefore, 11b HSD-2 acts to prevent placental diffusion of GC (Seckl 2001, Clarke et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…11b HSD-2 deactivates cortisol through conversion to the less active cortisone (Stewart et al 1995, Klemcke & Christenson 1996, Clarke et al 2002. Placental 11b HSD-2 is particularly important because maternal GC levels are up to tenfold higher than in the fetus, therefore, 11b HSD-2 acts to prevent placental diffusion of GC (Seckl 2001, Clarke et al 2002. Placental 11b HSD-2 is downregulated in response to maternal undernutrition, protein deficiency, reduced oxygen conditions, to chemicals such as glycyrrhizic acid and through mutation of the 11b HSD-2 gene (Dave-Sharma et al 1998, Bertram et al 2001, Alfaidy et al 2002.…”
Section: Introductionmentioning
confidence: 99%